High-grade fetal adenocarcinoma of the lung misdiagnosed as male breast carcinoma: a case report and literature review - Zhuo, Yuejian; Xu, Yanran; Qin, Rong; Guo, Min; Zhang, Dongdong (Frontiers in Oncology, 2023)
Background and aim High-grade fetal adenocarcinoma of the lung (HG-FLAC) is a specific subtype of lung adenocarcinoma with a poor prognosis. A lack of understanding exists because of the rarity of this disease. This study aimed to present a case of HG-FLAC with multiple metastases misdiagnosed as male breast carcinoma at the initial diagnosis. Case presentation The patient visited our hospital due to a month-long cough. The chest computed tomography (CT) scan revealed a mass in the left lung and chest wall, accompanied by enlargement of mediastinal lymph nodes. The magnetic resonance imaging indicated potential metastatic lesions in the brain and adrenal glands. The patient underwent a biopsy of the lesion in the right chest wall. The pathological and immunohistochemical findings indicated a high possibility of male breast cancer. However, the clinical features did not support this diagnosis. Therefore, a CT-guided percutaneous lung biopsy was performed, and the pathological examination finally indicated HG-FLAC. Conclusions We presented a complex yet interesting case in which HG-FLAC was misdiagnosed as male breast cancer. Our interesting case may stimulate discussions about the methods to manage patients with HG-FLAC.